IMPROVING THE CAPACITY OF PREGNANT WOMEN WITH “PEKAN BUMI BERCERITA” IN KALISONGO VILLAGE, MALANG - Yudianti, Ika; Mardiana, Heppy; Kusuma, Ratih (Universitas Airlangga, 2024)
The 2005-2025 National Long-Term Development Plan has placed the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) as indicators of health levels and the success of implementing health development. Therefore, there needs to be an innovative program to empower pregnant women with